THE INFLUENCE OF RISK-BASED BANK RATING (RBBR) METHOD ON PROFITABILITY OF PRIVATE-OWNED BANKS IN INDONESIA - Ponto, Monica .; Lambey, Linda .; Tumiwa, Johan . (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: The banking sector plays an important role in supporting and increasing the economic rate in country. Bank with high level of soundness is a bank that can perform its functions well, therefore, optimal management of the banking sector can provide economic stability in a developed country and make developing countries ready to compete economically of both national and international level. This study is aimed to determine the influence of Risk-Based Bank Rating (RBBR) Method on Profitability of Private-Owned banks in Indonesia. In this study, population refers to the banks listed in Indonesia Stock Exchange, using purposive sampling technique and sample size of 6 Private-Owned Banks that have total assets more than 100 trillion in rupiahs. By using multiple regression analysis method, the result and conclusion show that Credit Risk, Market Risk, Liquidity Risk, Earnings and Capital simultaneously and significantly influence Profitability of 6 Private-Owned Banks in Indonesia.  Furthermore, Market Risk and Earnings have significant and positive influences on Profitability. Credit Risk and Liquidity Risk have significant and negative influences on Profitability. Nevertheless, Capital has no significantly influence on Profitability. The banks’ management must consider the importance of the risk management because those factors above have effect banks profitability. Keywords: risk-based bank rating, profitability